Overcoming the Thermal Instability of Efficient Polymer Solar Cells by Employing Novel Fullerene‐Based Acceptors. Issue 3 (17th October 2016) - Zhang, Chaohong; Mumyatov, Alexander; Langner, Stefan; Perea, José Darío; Kassar, Thaer; Min, Jie; Ke, Lili; Chen, Haiwei; Gerasimov, Kirill L.; Anokhin, Denis V.; Ivanov, Dimitri A.; Ameri, Tayebeh; et al.
Abstract : Solution‐processed organic solar cells with promising photovoltaic performance and extraordinary high thermal stability are achieved by employing novel fullerene‐based acceptors in combination with two state‐of‐the‐art polymer donors. The findings demonstrated in this work underline the necessity and importance of novel acceptor design rules for highly efficient organic solar cells with excellent device stability.